Evaluation of Anti-Arthritic Effect of Red Sandalwood and Curcumin Combination (Orthorev Oil)® on Topical Application in Rats - Dawane, Jayshree Shriram; Dhande, Priti Pravin (Indian Journal of Pharmaceutical Education and Research)
Background: Arthritis, a common and debilitating condition characterized by joint inflammation, pain, and stiffness, affects millions of individuals worldwide. The standard treatment for arthritis is effective, but often comes with significant side effects and may not be suitable for long-term use. Aim: To evaluate the anti-arthritic effects of topical application of Orthorev Oil ® containing a combination of red sandalwood and curcumin in a rat model of arthritis. Materials and Methods: Wistar rats weighing 200-250 g were included in the study. Ethical Approval obtained from the institutional animal ethics committee. Baseline Measurements readings taken for paw volume using a plethysmometer. Arthritis induced with in Complete Freund's Adjuvant 0.1 mL injected into the plantar surface of the left hind paw of each rat. The rats observed for signs of arthritis development, typically characterized by paw swelling and redness, within few days. Treatments as per the groups given topically to each rat once daily for 21 days. The rats in the vehicle control group received the ointment base without active ingredients. The paw volume measured on days 0, 7, 14, and 21. Results: Significant increase in paw volume in comparison with control indicated the development of arthritis. Topical application significantly decreased paw volume in drug treated groups along with reduction in inflammatory markers. Conclusion: The topical application of Orthorev Oil® containing Red Sandalwood and Curcumin demonstrated significant anti-arthritic effects in a rat model of paw oedema along with reduction in inflammatory markers- TNF-α, IL-6, and CRP.
Keywords: Topical; Rheumatoid arthritis; Paw volume; Red sandalwood; Curcumin